Diego Hurtado de Mendoza, La ciencia argentina. Un proyecto inconcluso: 1930-2000 - Sandra Sauro (Prismas, 2011)
Diego Hurtado de Mendoza, La ciencia argentina. Un proyecto inconcluso: 1930-2000, Buenos Aires, Edhasa, 2010, 256 páginas